Morphology of the submandibular gland's acini of rats in diabetes mellitus - N. S. Tokaruk; O. H. Popadynets; V. I. Bedei; M. I. Hryshchuk; T. L. Kotyk (Zaporozhye State Medical University, 2020)
Aim. The purpose of the study was to determine the morphological changes in seromucous acini of the submandibular gland in experimental rats with diabetes mellitus. Material and methods. The experiment was performed with 1-year-old male Wistar rats. Experimental diabetes mellitus was induced by a single intraperitoneal administration of streptozotocin. Ultrastructural changes in the seromucous cells of the submandibular gland were studied during the 14th, 42nd and 70th days of the experiment. Results. In experimental diabetes mellitus in the seromucous cells of the submandibular gland hypertrophy of the rough endoplasmic reticulum and the Golgi complex; vacuolization of the cytoplasm; a large number of intracellular laminated structures and lysosomes; diffuse homogenization of the matrix, destruction of mitochondrial cristae and vacuolization of mitochondria were observed and the most pronounced on the 14th day. On the 70th day of the experiment the seromucous cells are characterized by the absence of morphological signs of damage and the development of atrophy and it is confirmed by the reduction in cells' size as well as the normalization of the relative area of secretory granules. Conclusion. The obtained data indicate that the reaction of the cells of seromucous acini to the development of hyperglycemia is typical and nonspecific. Thus, the alternative changes have a pronounced dystrophic character in the early stages and increase to the 42nd day of the experiment. On the 70th day histologic adaptation of the seromucous acini was observed and approved by atrophic changes, decrease of cells' area and normalization of the relative area of their granules.